2023
DOI: 10.1002/marc.202300060
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design and Research Progress of Thermally Conductive Polyimide Film – A Review

Abstract: Currently, heat accumulation has seriously affected the stabilities and life of electronic devices. Polyimide (PI) film with high thermal conductivity coefficient (𝝀) has long been held up as an ideal solution for heat dissipation. Based on the thermal conduction mechanisms and classical thermal conduction models, this review presents design ideas of PI films with microscopically ordered liquid crystalline structures which are of great significance for breaking the limit of 𝝀 enhancement and describes the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 179 publications
0
5
0
Order By: Relevance
“…The gray area in Figure 5b indicated that PIY film could not achieve the tensile strength of 69.73 MPa. [13] Obviously, hybrid PI films all exhibited typical tensile stress-strain curves for ductile materials. PI-PIY-30 had the best mechanical properties, with the tensile strength of 109.08 MPa, elongation at break of 13%, elastic modulus of 1.19 GPa, and the tensile strength was 5% and more than 56% higher than that of PI and PIY.…”
Section: Mechanical Properties Of Hybrid Pi Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gray area in Figure 5b indicated that PIY film could not achieve the tensile strength of 69.73 MPa. [13] Obviously, hybrid PI films all exhibited typical tensile stress-strain curves for ductile materials. PI-PIY-30 had the best mechanical properties, with the tensile strength of 109.08 MPa, elongation at break of 13%, elastic modulus of 1.19 GPa, and the tensile strength was 5% and more than 56% higher than that of PI and PIY.…”
Section: Mechanical Properties Of Hybrid Pi Filmsmentioning
confidence: 99%
“…[12] The equipment is facing increasingly demanding requirements of working conditions, for example continuous work in high humidity DOI: 10.1002/marc.202300510 environment will seriously affect the stability and life of electronic devices. [13] The intrinsic water contact angle (WCA) of pure PI films is low (≈50°-80°), unable to meet the requirements of hydrophobic properties for IC chip packaging and flexible wearable devices. [14][15][16][17][18][19][20] Therefore, it is necessary and meaningful to improve the hydrophobic properties of PI films from the perspective of intrinsic structure and surface microstructure design while ensuring excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The least conductive plane exhibited a thermal conductivity of 18.4 W m −1 K −1 , while the highest conductive plane had a thermal conductivity of 60 W m −1 K −1 . The films prepared through these hot stretching processes appear to comprise self-assembled nanofibers, likely attributed to inter-chain van der Waals couplings 118,245 —additionally, Xiang et al 124 investigated the effects of drawing on PI fibers and observed changes in crystallinity size, which increased from an initial 3.85 nm to 9 nm.…”
Section: Molecular Scale Effects For Thermal Transport In Polymersmentioning
confidence: 99%
“…Its exceptional heat resistance is particularly desirable for heat transfer applications, as it effectively maintains its structural integrity even when exposed to high temperatures. [21,22] Varying concentrations of nanoparticles were employed to fabricate hybrid nanofibers, enabling us to investigate the influence of nanoparticle content on morphology, thermal conductivity, and mechanical properties. Importantly, scanning thermal microscopy (SThM) and thermal camera imaging were employed to assess the thermal properties.…”
Section: Introductionmentioning
confidence: 99%